2015
DOI: 10.1002/mats.201500025
|View full text |Cite
|
Sign up to set email alerts
|

Toward a General Methodology for Modeling Diffusive-Controlled Reactions in Free Radical Polymerization

Abstract: A mathematical model for describing the bulk free‐radical polymerization of methyl‐methacrylate was developed. This model includes a novel methodology for describing the diffusive step of the kinetic rate coefficients, which is based on geometric considerations and application of the Einstein diffusion Equation. The effect of polymer content and temperature on the Rp behavior is discussed in terms of the evolution of the interdependent parameters defining the Rp. The applicability of Smoluchowski equation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(58 citation statements)
references
References 37 publications
4
54
0
Order By: Relevance
“…As far as the authors know, there is no another mathematical model reported in the literature that can predict such minimum. This latter has also been observed in the bulk free‐radical polymerizations of MMA and VAc, as it was reported in references …”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…As far as the authors know, there is no another mathematical model reported in the literature that can predict such minimum. This latter has also been observed in the bulk free‐radical polymerizations of MMA and VAc, as it was reported in references …”
Section: Resultssupporting
confidence: 82%
“…The aim of this work is to study the kinetics of bulk‐FRP of the butyl methacrylate isomers on the base of R p measurements obtained by DSC and to discuss the results with the aid of simulations using a mathematical model previously reported by two of the authors . In this context, differences and similarities with work reported by Buback and Junkers regarding kinetic aspects of the FRP of the monomers under studied, are discussed.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the present work, an alternative explanation for the effect of a CTA on the autoacceleration effect is proposed. This hypothesis is based on simulations of the bulk free‐radical polymerization using a modified version of a mathematical model recently reported by the authors and validated with experimental data reported in the literature in which the effect of the CTA concentration on the kinetics was studied using 2,2′‐azobisisobutyronitrile (AIBN) as initiator.…”
Section: Introductionmentioning
confidence: 71%